Implementation of AI-Based Digital Platform Through Canva Application in Indonesian Language Subject for Students of SMP Negeri 15 Manado - Wijaya, Pratiwi Wardini Putri; Ratu, Donald M.; Iroth, Santje (Abdurrauf Science and Society, 2025)
This study aims to explore the application of the Canva application in Indonesian language learning at SMP Negeri 15 Manado, especially in creating poster designs by grade VII students. Through a descriptive qualitative approach, this study involved observation, interviews, and documentation to analyze the effectiveness of Canva as a learning medium. The results showed that the majority of students were able to convey messages well through the posters they made, with many of them getting the predicate "Very Good" (A) and "Good" (B). Students' abilities were seen from the use of attractive colors and neat layouts, although there were some minor errors in language and spelling. The assessment was carried out based on a rubric that included the suitability of content, creativity, layout, use of color and images, and language and spelling. This study identified challenges and opportunities in implementing Canva, as well as its benefits in improving 21st century skills, such as creativity and collaboration. It is hoped that the results of this study can contribute to the development of more innovative and effective learning methods.